2008
DOI: 10.2320/matertrans.mra2007318
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Rolling Conditions in Mg–Al–Ca Alloy Containing Insoluble Second Phase Particles

Abstract: Hot rolling was conducted for Mg-6 mass%Al-2 mass%Ca alloy containing insoluble second phase particles and the mechanical properties of the rolled sheets were examined. The alloy used for rolling contained spherical particles with the size of 1.5 mm mainly in the grain boundaries. The amount of edge crack in the rolled sheets decreased at the rolling temperatures above $ 623 K. The highest strength and moderate elongation were obtained when the alloy was rolled at 623 K. The processing conditions for good work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It is known that the diffusion coefficient is much lower for low angle grain boundary; 27) however, the OIM of hot-compressed Mg-9Al-1Zn-1Ca in Fig. 8 shows that the misorientation angle of grain boundary was mostly higher than 15 , although a small portion of low angle grain boundary existed. Therefore, a general D GB value was adopted from Ref.…”
Section: Effect Of Initial Microstructure On Drx Of Mg Alloysmentioning
confidence: 90%
See 1 more Smart Citation
“…It is known that the diffusion coefficient is much lower for low angle grain boundary; 27) however, the OIM of hot-compressed Mg-9Al-1Zn-1Ca in Fig. 8 shows that the misorientation angle of grain boundary was mostly higher than 15 , although a small portion of low angle grain boundary existed. Therefore, a general D GB value was adopted from Ref.…”
Section: Effect Of Initial Microstructure On Drx Of Mg Alloysmentioning
confidence: 90%
“…9) Until now, there are some studies on dynamic recrystallization and mechanical properties of the Mg-Al-Ca alloys. 9,[11][12][13][14][15] In the present paper, continuously-casted Mg9Al-1Zn-1Ca and Mg-9Al-1Zn (in mass%) alloys with relatively coarse grain size (¼ 150{300 mm) are forged by hot compression at 573 K. DRX behavior during the hot compression is examined from the viewpoint of initial microstructures (distribution of second phases and Al segregation 16) ). The superplastic properties of the forged alloys are also investigated by tension tests at 573 K.…”
mentioning
confidence: 99%
“…In general, Mg alloys that contain other elements are known to have greatly enhanced mechanical properties, but their ductility can be maintained only processing the cast metal through extrusion and/or plastic deformation [10][11]. It has been suggested that grain refinement of the Mg phase occurs during extrusion deformation [3,[10][11][12]. The strength and microstructure of extruded Mg-Ca and Mg-Ca-Al(Zn) [6][7][9][10][11][12][13] alloys have been examined, together with the distribution of compounds within these materials [7,12,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that grain refinement of the Mg phase occurs during extrusion deformation [3,[10][11][12]. The strength and microstructure of extruded Mg-Ca and Mg-Ca-Al(Zn) [6][7][9][10][11][12][13] alloys have been examined, together with the distribution of compounds within these materials [7,12,15]. Most of the plastic deformation processes to which Ca-containing Mg alloys have been subjected are extrusion processes [9][10], and there have been few attempts to examine improvements in the strength of these materials by means of rolling and working processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation